Penelusuran Bahan Pustaka online Melalui Internet di Perpustakaan Jurusan Biologi FMPA UNM - Andi Faridah, A research report of the composition of (bionature, 2011)
Text book owned by the Biological Library of FMIPA UNM able to fulfill 70% requirement of student literature and 100% requirement teach by the teacher. Along with science progress in biological area, text book owned by the library require to be improved. But addition sum up the book did not correct solution because the addition sum up the book need the broader place, more amount time, and larger ones energy to manage the books. Biological Library of FMIPA UNM have the additional service that is service free acces internet. To assist the student to search of online study literature, researcher conduct the mentoring toward library visitor (student). This mentoring will know: "How many improvement of library visitor in Biological Library of FMIPA UNM after mentoring online library?". Research method is: research of literature, observation, mentoring, quetionnaire, and evaluation. Result of research find that afterÂ  mentoring the amount of library visitor have increase so much. This matter caused by almost the all visitor did not yet known searching of book online and also the book fulfill requirement of academic student. Therefore to increase service of Biological Library of FMIPA UNM, the management must provide free access the internet, computer, speed access, and mentoring base on the requirement of academic student.Â